HUBUNGAN BODY IMAGE DENGAN POLA KONSUMSI DAN STATUS GIZI REMAJA PUTRI DI SMPN 12 SEMARANG - Dina Happy Yusinta; Siti Fatimah Pradigdo; M. Zen Rahfiluddin (Jurnal Kesehatan Masyarakat (Undip), 2019)
An adolescent especially girl have a tendency to trying to lose weight for the ideal body they want to achieve. Food consumption that is not good will result in the nutritional status of adolescents. This research was conducted to analyze the relationship between body image and with food consumption and nutritional status of female adolescents at 12 Junior High School Semarang. This study was a quantitative observational study using a cross sectional study on 65 female students at 12 Junior High School Semarang selected by simple random sampling. Body image data was obtained with the MBSRQ-AS Multidimensional Body Self Relation Questionnare Apprearance Scales questionnaire, food consumption with Food Frequency Questionnaire (FFQ), and nutritional status with IMT according to age and analyzed using Rank Spearman. The results showed that most of the students were 14 years old (75.4%), negative body image (body image) 47.7%, consumption patterns were not good 90.8% and malnutrition nutritional status was 21.5%. There is no relationship between body image (Body image) and consumption patterns (p = 0.981) and there is no relationship between food consumption and nutritional status (p = 0.938). The need for further research to determine the factors that influence the consumption and nutritional status of adolescent especially girl in 12 Junior High School Semarang